THE NURSE IN THE CARE OF NURSING PROFESSIONALS DIAGNOSED WITH ANXIETY (REMUNOM, 2026)
Anxiety has been recognized as one of the main manifestations of mental distress among nursing professionals, frequently associated with adverse working conditions, high care demands, institutional insecurity, and the daily challenges of professional practice. In this context, nurses not only perform caregiving functions but also act as managers, leaders, and caregivers for the team, playing an important role in promoting mental health and supporting professionals who present symptoms or a diagnosis of anxiety. This study aimed to understand the role of nurses in caring for nursing professionals diagnosed with anxiety, considering their care strategies, interventions, and the challenges faced in the workplace. This is an integrative literature review based on the analysis of 13 scientific articles obtained from the SciELO, PubMed, and Google Scholar databases. The search included publications from the last five years, in Portuguese and English, related to mental health, anxiety, and the role of nurses in the nursing context. Studies available in full, with observational, descriptive, or cross-sectional designs were included. The results indicated a high prevalence of anxiety symptoms among nursing professionals, mainly associated with work overload, long working hours, fear of contamination, insecurity regarding care protocols, and insufficient institutional support. It was evident that nurses play a fundamental role in the early identification of these signs through qualified listening, behavioral observation, and open communication with the team. Among the main care strategies highlighted were individualized support, referral for psychological counseling, the creation of spaces for dialogue, and encouragement of self-care practices. It is concluded that nurses occupy a strategic position in the mental health care of the team, and that strengthening institutional policies and working conditions that promote well-being and quality of care is essential.